Synthesis of porous Hydroxyapatite (HAp) from Laying Chicken Waste Eggshells - Agung Rimayanto Gintu; Elizabeth Betty E. Kristiani; Yohanes Martono (RAFFLESIA JOURNAL OF NATURAL AND APPLIED SCIENCES, 2022)
Hydroxyapatite (HAp) was the type of bioceramics synthesized from the compound which rich Calcium (Ca) contains, these bioceramics commonly used to repair the damage of hard tissues. In this study threatened the synthesis of HAp from laying chicken eggshells, the characterization of the eggshells showed that the contains of Calcium 0,9809 ± 0,0118g/g; Phosphate 0,0236 ± 0,0009g/g; and ratio of Ca/P 2,0840%. The synthetic process by base precipitation method showed the yield 77,5786 ± 0,3509%; and from the synthetic obtained the HAp with contains of Calcium 0,1522 ± 0,0047g/g; Phosphate 0,01354 ± 0,0019g/g; and ratio of Ca/P 0,9162%. The Biochemical characterization of the HAp showed that the Porosity 70,5940 ± 0,4104%; Biodegradability 16,1879 ± 0,1362%; and swelling Ability 28,0549 ± 0,1054%. The entire result of the research concluded that the sample eggshells potentially became one of the sources of HAp, and the HAp synthesized from the eggshells potentially to apply as remineralization agents.